KOMPETENSI PEDAGOGIK GURU DI SMP NEGERI 1 DAN 2 KECAMATAN NAN SABARIS KABUPATEN PADANG PARIAMAN (Study Komparatif Senior dan Guru Junior) - Agusnita (Jurnal Bahana Manajemen Pendidikan, 2015)
The goal of this research are to know information about the pedagogical competence (comparison study senior and junior teachers). The population is 73 teacher and the sample is 57 people that taken by disproporsional random sampling. The instrument of this research is Likert scale models that had validity and reliability. Data analyzed using t test. The result of this research are the to there is significant deffrent pedagogical competence di SMP Negeri 1 dan 2 kecamatan nan sabaris Kabupaten Padang Pariamn between senior and junior teachers.Key word : senior and junior teachers